STUDI EFEKTIVITAS AUDIT INTERNAL DALAM UPAYA MITIGASI TINDAKAN FRAUD DI INSTITUSI PEMERINTAHAN - Anggara, Berwin; Ariani, Siti Septi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study was to examine the impact of internal audit effectiveness and its success factors (Independence, Internal Control, Professionalism, and Competence) on fraud prevention in the Metro City Inspectorate. The research utilized quantitative methods and involved 31 respondents. Data collection was conducted using a questionnaire distributed to Functional Auditor Positions (JFA) who had worked at the Metro City Inspectorate for over a year. The collected data was tabulated and subjected to classical assumptions testing, multiple linear regression tests, and hypothesis testing using SPSS Statistics 26. The study findings revealed that the effectiveness of internal audit, specifically the independence of internal auditors, did not significantly affect fraud prevention. However, internal control and auditor competence were found to influence fraud prevention. Professionalism, on the other hand, showed no significant impact on fraud prevention. The simultaneous test indicated that independence, internal control, professionalism, and competence collectively had an impact on fraud prevention